Kontinuitas Filsafat Islam: Manhaj Ahli Falsafah Sebagai Jembatan Antara Tradisi dan Inovasi Pemikiran - Nur Muh Zaid Zulkarnaen; Najwa Fila Shofa; Lailani Fauzia; Mujibur Rohman; Ahmad Muthohar (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
This research reviews the problem of continuity in Islamic philosophy by focusing on the crucial role of philosophers as a bridge between tradition and innovation of thought. In facing the complexity of contemporary developments, Islamic philosophers are faced with the challenge of maintaining a rich intellectual heritage without sacrificing the ability to innovate. In this context, philosopher's manhaj is not only a method of intellectual research, but also a philosophical strategy for designing a balanced approach between maintaining traditional values ”‹”‹and responding to the demands of contemporary thought. This research uses a qualitative research method with a literature study approach. This research takes data from various sources such as books, academic journals, or online sources, to identify themes, patterns, and trends related to research questions or topics on the continuity of Islamic philosophy: the manhaj of philosophers as a bridge between tradition and innovation of thought. This research analyzes the traditional heritage in Islamic philosophical thought, the innovation and development of contemporary thought, and the continuity in contemporary challenges. In conclusion, the philosopher's manhaj is described as an important tool in maintaining the continuity of Islamic philosophy, helping to create relevant and ethical thinking for the present without losing its traditional roots.